SIFAT KIMIA TANAH DI BAWAH VEGETASI MANGROVE DI DESA LEBITI KECAMATAN TOGEAN KABUPATEN TOJO UNA-UNA - Arsad, Wirsam M; Toknok, Bau; Korja, I Nengah (ForestSains, 2017)
Similar to the soils in other ecosystems, mangrove soil has natural characteristics as benchmark to identify its potential and productivity.The aim of this study was to investigate the chemical properties of soil below mangrove vegetation in Lebiti Village, Togean District, Tojo Una-Una Regency, which was detemined as the study area. This study was conducted in November 2015 to January 2016. Samples were selected by purposive sampling method in which both of soil and water were obtained from each type of mangrove vegetation in the study area. Soil sampling was done twice on each type of mangrove vegetation and collected by using PVC pipe of 2.5 inches with a length of 60 cm, while water was taken and stored in mineral water bottle. The entire samples were analyzed at the Soil Science Laboratory, Faculty of Agriculture, Universitas Tadulako. Based on the field study, there were three types of mangrove vegetation, namely Sonneratia caseolaris, Bruguiera gymnorrhiza, and Rhizophora apiculata. The analysis on chemical properties demonstrated the pH was acidic to acidic (5.18 to 6.37), Nitrogen (total N) was moderate to very high (0.38% to 0.89%), phosphorus (available-P) was very low to high (1.78 to 16.69 ppm), potassium (available-K) was low to high (0.12 to 0.82 (cmol(+)kg-1)), Carbon (organic-C) was very high (2.08 to 9.30%), cation exchange capacity (CEC) was very (23.76 to 47.68 (cmol(+)kg-1)), and the levels of salinity was high (3.2 to 3.3 ppt).